Eastern Region Transport Survey Volume VII Pricing Policy, Cost Comparisons and Traffic Allocation September, 1967 - Planning Commission (Planning Commission, 1967)
This summary reviews Volume VII of the Eastern Region Transport Survey, which examines transport pricing policies, cost comparisons, and traffic allocation strategies to improve transport efficiency in India’s Eastern region. The study advocates cost-based pricing that reflects economic costs and capacity utilization, highlighting the relative efficiency of rail transport for bulk commodities and the role of service characteristics in modal choice. It also evaluates alternative port options to address congestion and optimize freight movements. Complementary analysis of petroleum and steel pricing, import duties, excise taxes, and exchange rate adjustments underscores their significant impact on transport costs and investment decisions. Together, the findings provide a comprehensive framework for informed transport policy formulation, infrastructure investment, and efficient resource allocation to support regional economic growth.
Regional Transport Survey Unit, Eastern Region, Calcutta Planning Commission Goverment of India, September, 1967
Regional Transport Survey Unit, Eastern Region, Calcutta Planning Commission Government of India, September, 1967
Keywords: Eastern Region Transport Survey; Transport Pricing Policy; Cost Comparison Analysis; Traffic Allocation; Rail And Road Transport; Economic And Financial Costs; Port Diversion Strategy; Petroleum Product Pricing; Import And Excise Duties; Transport Infrastructure Planning